Odpowiedź:
a)
6 - 5 [tex]\frac{3}{4}[/tex] = [tex]\frac{1}{4}[/tex]
b)
-4 [tex]\frac{2}{9}[/tex] - 2 [tex]\frac{4}{9}[/tex] = -6 [tex]\frac{6}{9}[/tex] = 6 [tex]\frac{2}{3}[/tex]
c)
7 [tex]\frac{5}{6}[/tex] - 1 [tex]\frac{1}{6}[/tex] = 6 [tex]\frac{4}{6}[/tex] = 6 [tex]\frac{2}{3}[/tex]
d)
3 [tex]\frac{2}{5}[/tex] - 4 [tex]\frac{1}{5}[/tex] = - [tex]\frac{4}{5}[/tex]
e)
2 [tex]\frac{3}{4}[/tex] - 3 [tex]\frac{1}{2}[/tex] - 4 [tex]\frac{2}{3}[/tex] =
2 [tex]\frac{9}{12}[/tex] - 3 [tex]\frac{6}{12}[/tex] - 4 [tex]\frac{8}{12}[/tex] =
2 [tex]\frac{9}{12}[/tex] - 8 [tex]\frac{2}{12}[/tex] - 5 [tex]\frac{5}{12}[/tex]
f)
65 - 38 - 21 + 19 + 51 - 41 =
65 + 12 + 51 - 38 - 21 - 41 =
128 - 100 = 28